Area effect during the fracture process of high-Niobium-Titanium-Aluminum alloys under continuous tension loading-unloading - Zhong, Mingjie; Lin, Youzhi (Frontiers in Materials, 2023)
Based on the extracted results of the continuous tension loadingunloading testing, and observations of the corresponding cracks and fracture surfaces for the high-Niobium-Titanium-Aluminum alloys, both tensile damage and fracture mechanism were systematically studied.From the acquired results, it was demonstrated that the continuous tension loading-unloading did not affect the elastic modulus of the alloy.However, it decreased in fracture stress, fracture strain, and fracture work per unit area, and increased in irreversible strain. This result shows that the irreversible strain is not mainly caused by the volume effect of microcracks, but by the plastic strain of the materials. Although the density of the micro-cracks produced by multi-loading and unloading was small, most of the micro-cracks were concentrated on a certain section area, which results in an obvious area effect caused by the damage of the microcrack. In addition, the further propagation of the main crack under lower re-loading stress was not caused by the application of higher normal stress but by the residual tensile stress, which depends on the deterioration of the material at the crack tip during the unloading process of the alloy. These small amounts of microcracks are usually concentrated on the cross-sectional area, and the area effect caused by the microcracks damage is also obvious, which leads to a reduction of the fracture performance. Therefore, the area effect ultimately induces a decrease in fracture stress.